(untitled) (Itinera, 2016)
In just a few decades, there’s been the birth and fast rise of a recreational activity that implies the interaction between one or multiple players with electronic devices, normally, known as videogames. Being a very complex process and a multi-sensorial practice, playing with videogames produces intense and fulfilling experiences for all those who engage in such activity. Here, I intend to show how those experiences entail relevant aesthetic – and also cognitive and ethical – values for philosophical discussion.